2017
DOI: 10.1074/jbc.ra117.000123
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory activity of curcumin is mediated by its oxidative metabolites

Abstract: The spice turmeric, with its active polyphenol curcumin, has been used as anti-inflammatory remedy in traditional Asian medicine for centuries. Many cellular targets of curcumin have been identified, but how such a wide range of targets can be affected by a single compound is unclear. Here, we identified curcumin as a pro-drug that requires oxidative activation into reactive metabolites to exert anti-inflammatory activities. Synthetic curcumin analogs that undergo oxidative transformation potently inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
144
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 63 publications
5
144
0
Order By: Relevance
“…However, by using an experimental setup that allowed in situ formation of the autoxidized products, Edwards et al found that NF‐κB inhibition by curcumin depends on oxidative activation, and that this is due to the reactive electrophile intermediates covalently binding to signaling proteins, such as for example IKKβ. Very interestingly, and in line with the perspective discussed here, they could clearly connect this activity to the oxidative status of the cells, in other words, they demonstrated that oxidative stress modulates curcumin's bioactivity through the in situ formation of oxidized intermediates …”
Section: Biological Significance Of Rons Scavenging‐related Antioxidasupporting
confidence: 82%
See 3 more Smart Citations
“…However, by using an experimental setup that allowed in situ formation of the autoxidized products, Edwards et al found that NF‐κB inhibition by curcumin depends on oxidative activation, and that this is due to the reactive electrophile intermediates covalently binding to signaling proteins, such as for example IKKβ. Very interestingly, and in line with the perspective discussed here, they could clearly connect this activity to the oxidative status of the cells, in other words, they demonstrated that oxidative stress modulates curcumin's bioactivity through the in situ formation of oxidized intermediates …”
Section: Biological Significance Of Rons Scavenging‐related Antioxidasupporting
confidence: 82%
“…In their response, the authors disapproved this theory and presented evidence for the inactivity of 1za and 1zc for suppressing the activation of NF‐κB, in contrast with the case of curcumin . While the clinical relevance of the above‐mentioned recent findings by Edwards et al on this pathway is unclear, one could hypothesize a similar oxidative stress‐related formation of reactive intermediates.…”
Section: Biological Significance Of Rons Scavenging‐related Antioxidamentioning
confidence: 98%
See 2 more Smart Citations
“…It is worth noting that curcumin is the major active compound of the plant with no distinguishable toxicity . Recent studies have shown that curcumin has antiviral, antibacterial, anti‐inflammatory, and antioxidant activities. Furthermore, the therapeutic effects of curcumin and curcumin derivatives have been proven in numerous diseases such as endometriosis, Crohn's disease, pulmonary diseases, cardiac diseases, and kidney diseases .…”
Section: Introductionmentioning
confidence: 99%